2022
DOI: 10.1126/sciadv.abn6928
|View full text |Cite
|
Sign up to set email alerts
|

The requirement of phosphoenolpyruvate carboxykinase 1 for angiogenesis in vitro and in vivo

Abstract: We here examined the potential biological function of phosphoenolpyruvate carboxykinase 1 (PCK1) in angiogenesis. shRNA- or CRISPR-Cas9–induced PCK1 depletion potently inhibited endothelial cell proliferation, migration, sprouting, and tube formation, whereas ectopic PCK1 overexpression exerted opposite activity. In HUVECs, Gα i3 expression and Akt activation were decreased following PCK1 depletion, but were augmented by ectopic PCK1 overexpression. In vivo, retinal expression of PCK1 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
114
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(115 citation statements)
references
References 58 publications
(140 reference statements)
1
114
0
Order By: Relevance
“…An early study using luciferase reporter assay and chromatin Immunoprecipitation (ChIP) demonstrated that the transcription factor GATA4 can directly bind to the promoter region of Gαi3 and regulate its transcriptional activity and expression [33]. The very recent study of our group has shown that GATA4 is an important transcription factor of Gαi3 in endothelial cells [28]. We further discovered that phosphoenolpyruvate carboxykinase 1 (PCK1) associated with phosphorylated GATA4, promoting Gαi3 transcription and expression in endothelial cells [28].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…An early study using luciferase reporter assay and chromatin Immunoprecipitation (ChIP) demonstrated that the transcription factor GATA4 can directly bind to the promoter region of Gαi3 and regulate its transcriptional activity and expression [33]. The very recent study of our group has shown that GATA4 is an important transcription factor of Gαi3 in endothelial cells [28]. We further discovered that phosphoenolpyruvate carboxykinase 1 (PCK1) associated with phosphorylated GATA4, promoting Gαi3 transcription and expression in endothelial cells [28].…”
Section: Discussionmentioning
confidence: 99%
“…The very recent study of our group has shown that GATA4 is an important transcription factor of Gαi3 in endothelial cells [28]. We further discovered that phosphoenolpyruvate carboxykinase 1 (PCK1) associated with phosphorylated GATA4, promoting Gαi3 transcription and expression in endothelial cells [28]. It will then lead to increased Akt-mTOR activation and pro-angiogenesis response [28].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations